Perbandingan Metode Arima Box-Jenkins dan Holt-Winters No Seasonal pada Peramalan Jumlah Penderita ISPA di Kota Malang - Nanta Sigit; Arief Setiyoargo (Wiraraja Medika : Jurnal Kesehatan, 2021)
ISPA is an acute respiratory disease with special attention to pneumonia (ISPA), and not an ear and throat disease. In order to make plans to reduce the number of ISPA sufferers in the regions with effective and responsible principles, valid forecasts are needed. There is a relatively large difference between targets and achievements in tackling ISPA sufferers in Malang City during 2017 - 2020, and given the importance of forecasting as an indicator of reducing ISPA sufferers, it is deemed necessary to conduct research on the application of the Box-Jenkins model in forecasting ISPA patients. This study aims to create an estimation model for patients with ISPA in Malang Regency using data from the Health Office from 2017 to 2020. The analytical technique applied is the Box-Jenkins model or the Autoregressive Integrated Moving Average (ARIMA). The results showed that by using data from the Malang City Health Office from 2014 to 2019, it was concluded that the best forecasting model was ARIMA(1,1,0). Researchers hope that the forecasting method and forecasting results can be used as additional information for the health department in Malang City in determining policies that must be taken in the prevention of ISPA sufferers according to the needs of patients in Malang City.